Access to Information Resources by Students with Disabilities: Case Study Dar al-Hikmah IIUM Library - Pebrianti, Hera (Jurusan Ilmu Perpustakaan dan Informasi Islam Universitas Islam Negerin Datokarama Palu, 2023)
The aim of the researcher conducting this study is to identify library information resources for students with disability in Dar al-Hikmah Library International Islamic University Malaysia. This study has two research objective, the first, identifying the type of library information resources available for disabled students in Dar Al- and the second, identifying the factors influencing disabled students in using library information resources. This study adopts the descriptive survey design. Thus, this study used a questionnaire for data collection. The instrument was chosen since it was considered to be the most appropriate and reliable tool for this study. Afterwards, the data collection for questionnaire was done with the help of the staffs Disability Unit Services (DSU) and some disabled students colleagues in International Islamic University Malaysia. Firstly, the staff of DSU IIUM sent the questionnaire to the group undergraduate and postgraduate disabled students to be fulfilled. The second, some colleagues of disabled students also assisted to spread out the questionnaire with their fellows. From the 54 disabled students in IIUM Gombak, the targeted sample of this study merely around 20 % of that total students. Research results show that, the most common library resources found in Dar Al-Hikmah Library which are Braile Collection, Large Print, and Electronic Resources as well as Audiovisual & Multimedia Resources. The next, the library information resources preferred by special needs students in IIUM are Electronic Resources & Audiovisual & Multimedia Resources.